PENGARUH EKSTRAKURIKULER PANAHAN TERHADAP KONSENTRASI BELAJAR SISWA DI MTs BAITURRAHMAN TELUK KUANTAN KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Diki Yuwanda; Bustanur Bustanur; Sopiatun Nahwiyah (Universitas Islam Kuantan Singingi, 2020)
This research is motivated by the concentration of student learning that is still lacking during the learning process. In the MTs Baiturrahman area in Teluk Kuantan archery extracurricular activities have been carried out. Based on the background and phenomena above, this study aims to determine whether there is an effect of archery extracurricular on the concentration of student learning in MTs Baiturrahman Teluk Kuantan Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi. This research is a quantitative method research, which was carried out at MTs Baiturrahman Teluk Kuantan Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi. Data collection techniques used were questionnaire, interview and documentation. Data analysis used a statistical formula in the form of a simple linear regression analysis processed using SPSS Version 25 software. Based on the Significance value (Sig.) From the Coefficients table, the Significance value (Sig.) Obtained is 0,000 less than the probability of 0.05, meaning that the hypothesis is accepted. So it can be concluded that the Archery Extracurricular variable (X) influences the Learning Concentration variable (Y). So archery extracurricular influences the concentration of student learning in MTs Baiturrahman Teluk Kuantan Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi.